What is the required minimum number of high-rise buildings above which the prevalence of melanoma decreases? - Arbel, Yuval; Arbel, Yifat; Kerner, Amichai; Kerner, Miryam (Frontiers in Built Environment, 2025)
ObjectivesTo explore the relationship between the prevalence of melanoma adjusted for age and the number of skyscrapers.Study DesignThe study is based on data from 50 US states and a 19-year period (1999–2017).MethodAn interesting contribution is the use of quadratic regression model, which permits non-monotonic modification with the number of skyscrapers in the state.ResultsFor the 32 states with at least one skyscraper, results demonstrate an increase (a decrease) in anticipated prevalence of melanoma when number of skyscrapers is below (exceeds) 60 buildings.ConclusionAgglomeration of high-rise buildings, some of which are residential buildings, intensifies the shade effect and reduces reflection of radiation effect. Findings may be of assistance to public policy and city planners.